Keadilan, Diyat dan Pemaafan dalam Ayat Qiṣāṣ: Kajian Etis Terhadap Surah Al-Baqarah - Fachrul Mubaraq; Ferdi Hasayangan Dalimunthe; Muhammad Alviano (Indo Publishing, 2026)
Qisas is a form of punishment in Islamic criminal law imposed on perpetrators of murder and physical injury, based on the principle of equal retaliation. This study aims to explain the concept of qisas as stated in the Qur’an, particularly Surah al-Baqarah verses 178–179, and to examine its purpose in achieving justice, preventing crime, and protecting human life. This research employs a qualitative approach using library research methods. The data are collected from the Qur’an, classical Qur’anic commentaries, Islamic criminal law literature, and relevant scholarly articles. Data analysis is conducted through content analysis by examining Qur’anic verses and the opinions of scholars inductively. The findings indicate that qisas is the primary punishment for cases of murder and physical injury; however, Islam also provides an opportunity for forgiveness from the victim or the victim’s family through the payment of diyah (compensation). This provision shows that qisas does not merely emphasize retaliation but also contains values of justice, humanity, and compassion. The implementation of qisas aims to protect human life, prevent serious crimes, and establish justice and social order in society. Thus, qisas is an integral part of Islamic law that is oriented toward public welfare and the protection of the right to life